2018
DOI: 10.1002/ajb2.1091
|View full text |Cite
|
Sign up to set email alerts
|

Experimental warming advances phenology of groundlayer plants at the boreal‐temperate forest ecotone

Abstract: Climate warming will extend the growing season of groundlayer species in the boreal-temperate forest ecotone and alter the synchrony of their phenology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 56 publications
1
21
1
Order By: Relevance
“…We believe our data based on the long‐term in situ observations can be more trustworthy. In addition, our findings in the natural conditions are not consistent with the results based on climate change experiments that the manipulated climate warming causes extended LOS (Arfin Khan et al, ; Rice et al, ). This could be due to the differences in range of effect sizes, which is dependent on the number of global change drivers adopted in the experiments (Leuzinger et al, ).…”
Section: Resultscontrasting
confidence: 99%
“…We believe our data based on the long‐term in situ observations can be more trustworthy. In addition, our findings in the natural conditions are not consistent with the results based on climate change experiments that the manipulated climate warming causes extended LOS (Arfin Khan et al, ; Rice et al, ). This could be due to the differences in range of effect sizes, which is dependent on the number of global change drivers adopted in the experiments (Leuzinger et al, ).…”
Section: Resultscontrasting
confidence: 99%
“…This confirms our hypothesis that leaf out in herbaceous species would be less responsive than tree seedlings to changes in light quality during spring. This result reaffirms the suggestion that the main cues controlling spring emergence in herbaceous species, which are submerged belowground during winter, are probably the timing of snow melt and increase in soil temperature rather than light quality (Price and Waser 1998, Rice et al 2018). Herbaceous species were monitored less often and on a less detailed scale than A. platanoides meaning that subtle differences in their phenology could be overlooked.…”
Section: Discussionsupporting
confidence: 85%
“…More broadly, climatic warming can also alter the timing of bud‐break and leaf senescence in a variety of plant species, including canopy trees, shrubs, and summer‐green herbaceous plants (Norby et al., ; Jacques et al., ; McDonough Mackenzie et al., ; Rice et al., ; Livensperger et al., ; Zohner and Renner, ). Notably, other studies have demonstrated that plants in arctic, subalpine, and alpine settings can adjust their leaf phenology in response to temperature regime adjustments (Inouye, ; Hoffmann et al., ; Wipf, ; Krab et al., ; Rice et al., ; Richardson et al., ). These high altitude and latitude species share the lack of a closed canopy with spring ephemerals, and therefore parallel responses with this study augment the result of plant leaf phenology in high light species being responsive to early spring warming.…”
Section: Discussionmentioning
confidence: 99%
“…One result of this general warming trend is changes in the timing of the onset of seasons, including the arrival of spring (Groffman et al., ; Wilson, ). In response to this warming, some species have adjusted the timing of life history events including egg hatching, migrations, flowering, and fruiting (Badeck et al., ; Forrest et al., ; Wipf, ; Hänninen and Tanino, ; Wilson, ; Hansson et al., ; Bertin, ; Jacques et al., ; CaraDonna et al., ; Groner et al., ; McDonough MacKenzie et al., ; Rice et al., ; Daru et al., ).…”
mentioning
confidence: 99%